A systematic review assessing the dental pulp stone prevalence in the Saudi Arabian population - Sandeepa Nuchilakath Chalikkandy; Shilpa Bhandi; Hamed Ahmed Ali Al Shawkani; Mohammed Hussain Dafer Al Wadei; M. Mohammed Abdul Kader; Atlal Hassan Hussain Jaafari; Thilla Sekar Vinothkumar; Saranya Varadarajan; Luca Testarelli; Shankargouda Patil (Saudi Dental Journal)
This Systematic Review (SR) was to report on the prevalence of pulp stones in the Saudi Arabian (KSA) population. The electronic databases were searched for scientific research articles during May 2021. The data search was performed in electronic search engines like PubMed, Scopus, Web of science, and Saudi Digital Library, and 6 original research articles which fulfilled the eligibility criteria were assessed for qualitative data. The prevalence of pulp stones among the KSA population ranged from 4.6% to 50.93% among the study participants and it ranged between 10.2%−13.34% in the teeth assessed. The pulp stones were more frequently reported in decayed teeth, periodontal diseases, attrition, teeth with dental restorations, and higher in the molar teeth in comparison with the premolar teeth. The data on the prevalence of pulp stones among the Saudi population will be helpful for clinicians in planning endodontic procedures.